2015
DOI: 10.1177/009164711504300202
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Analyses of Three Measures of Grace: Can They be Unified?

Abstract: Grace is an interesting and potentially significant domain within positive psychology, but remains largely neglected. The present study examined the relationships among three known grace scales to evaluate the potential for creating a stronger single measure. It also explored their relationships to several other religious/spiritual measures to examine whether the three scales are measuring the same construct, to explore the implications for our understanding of grace, and to provide insights for further study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 32 publications
4
29
0
1
Order By: Relevance
“…Mean response scores for the three grace measures in the present study are similar to those reported by Bufford at al. (2015).…”
Section: Grace Measuressupporting
confidence: 91%
See 1 more Smart Citation
“…Mean response scores for the three grace measures in the present study are similar to those reported by Bufford at al. (2015).…”
Section: Grace Measuressupporting
confidence: 91%
“…The three grace scales showed significant correlations with each other (Bufford at al., 2015). The Grace scale showed significant positive correlations with spiritual well-being and both religious and existential well-being, gratitude, and positive religious coping; it showed negative correlations with internalized shame, negative religious coping, childhood adversity, and a measure of psychological distress (Bufford at al., 2015). The Richmont Grace Scale (RGS) showed this same pattern of correlations except that it did not correlate significantly with childhood adversity (Bufford, at al., 2015).…”
Section: Grace Measuresmentioning
confidence: 99%
“…Emmons et al ( 2017 ) noted that grace is “the gift of acceptance given unconditionally and voluntarily to an undeserving person by an unobligated giver... grace reflects a vital psychological need held by all people” (p. 276). Recently, grace has been investigated in a handful of quantitative studies in conservative Protestant populations (Bufford et al, 2015 , 2017 ; Judd et al, 2020 ). However, to date there have been no quantitative or qualitative studies that have focused explicitly on the aspects of how Catholics uniquely experience God’s divine grace, which is an ongoing and prominent aspect of Catholic life.…”
mentioning
confidence: 99%
“…Current instruments have heavily influenced by evangelical perspectives, and lack the methodological rigor expected in other areas within the psychology of religion (Bassett and the Roberts Wesleyan Research Group, 2013;Beckenbach et al, 2010;Bufford et al, 2015;Bufford et al, 2017;Hodge, 2020). Due to the growing diversity within Christianity as well as the transformation of language in an emerging postmodern society, standardized measures need to assess for an array of beliefs.…”
Section: Discussionmentioning
confidence: 99%